Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1055/s-0034-1377559
|View full text |Cite
|
Sign up to set email alerts
|

Core needle versus standard needle for endoscopic ultrasound-guided biopsy of solid pancreatic masses: a randomized crossover study

Abstract: The diagnostic accuracy of EUS sampling for solid pancreatic masses using standard and core needles seems comparable but with a better overall histological sample quality for the former. ClinicalTrial.gov identifier: NCT01479803.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 17 publications
5
93
2
Order By: Relevance
“…However, this study used suction during procurement of FNB, which may have increased the bloodiness and contamination of specimens. Two recently published prospective, randomized trials have also shown no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreas mass lesions [44,45]. Consistent with the previously published literature, results from this randomized controlled trial also showed no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreatic masses (FNB: 91.7 %, FNA: 78.4 %, P = 0.19).…”
Section: Discussionsupporting
confidence: 89%
“…However, this study used suction during procurement of FNB, which may have increased the bloodiness and contamination of specimens. Two recently published prospective, randomized trials have also shown no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreas mass lesions [44,45]. Consistent with the previously published literature, results from this randomized controlled trial also showed no difference in diagnostic yield between EUS-FNA and EUS-FNB for pancreatic masses (FNB: 91.7 %, FNA: 78.4 %, P = 0.19).…”
Section: Discussionsupporting
confidence: 89%
“…A similarly low negative predictive value (64%) was found previously in a study using core biopsy and cytoblock preparation [6]. To increase this value, a higher number of passes [11], a proper selection of adequate material [6] or guidance under contrast enhancement can be performed [21].…”
Section: Discussionmentioning
confidence: 54%
“…The procurement of visible core was obtained in all cases in our [4,6,10,22]. Conversely, there is one paper showing a diagnostic rate of 34% based on core biopsy with a 22G needle and five passes [23].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations